Transfer of Shares to Third Parties as an Event of Failure of Repo Transactions According to Pojk Number 9/Pojk.04/2015 - Andisa Sekarani Wibowo; Henni Wijayanti (International Journal Labs, 2023)
According to Article 1 number 1 of POJK No. 9/POJK.04/2015, the Repurchase Agreement Transaction hereinafter referred to as the Repo Transaction, is a contract to sell or buy securities with the promise of buying or selling again at a predetermined time and price. The essence of a repo transaction, that is, the Seller can buy back the securities he has sold to the Buyer at the price and at the specified time. However, such securities have often been sold by the Buyer to a Third Party before the expiration of the repurchase period. In this journal research, the author uses a case approach with a juridical-normative method, namely legal research carried out by examining library materials or secondary data as basic material for research by conducting a search for regulations and literature related to the subject matter under study. The results showed that the mechanism for transferring shares of Public Companies through repo transactions according to POJK No. 9 / POJK.04 / 2015 consists of 2 buying and selling transactions known as the first leg and second leg and is generally carried out through the negotiation market. Furthermore, the results showed that the transfer of MYRX shares by buyers to third parties was an event of repo transaction failure. The explanation of Article 3 paragraph (3) of POJK No. 9/POJK.04/2015 has outlined several circumstances that are classified as events of default, one of which is the failure to fulfill its obligations related to Repo Transactions. This is because the transfer of shares by the buyer to a third party causes the seller to be unable to repurchase the shares he has sold, so the Buyer fails to fulfill his obligation to resell the securities in the repo transaction to the Seller.